Dias de santos no lago Amanã: estudo histórico-antropológico de festejos do catolicismo ribeirinho amazônico - Loureiro, Luiz Francisco (2019)
This dissertation is a product of a historical-anthropological-oriented research about the catholic saints’ festivals that are carried out in riverine communities of the Amanã lake, in the middle Solimões river region. These religious popular celebrations comprise valuable social practices of the rural Amazonian culture. In them, participants have the possibility to revive both their devotion by religious rituals and their social bonds by the joyful gatherings that proceed them. Our main goal was, in order to understand its recent process of reproduction, to insert a perspective of duration in the observation of this social practice. Therefore, we started from the direct observation of the festivals held in the lake’s communities during the year of 2018, and looked for, by the application of interviews, knowing the history of the same festivals and elements of this social practice in the past, always favoring the temporary clipping of the past fifty years. Our results show a social practice biased, in its structure, by the sacred-profane duality, which also sets its present division into two different models and the coexistence of two very different significations. The saints’ festivals represented themselves as living records of the individual and collective agency of those who are committed to them. As a synthesis of its participants’ actions, these religious celebrations are marked by two central events of the lakes inhabitants’ recent history: the access-connection of the region in relation to close urban centers and the emergence of the social model of community organization. Based on this fact, we finally consider that the reproduction of this important immaterial heritage of the Amazon region depends, above all, on the guarantee of social reproduction for its practitioners.